We make a life by what we give - Gunderman, Richard B. (Philanthropic and nonprofit studies., 2008)
According to an old saying, "We make a living by what we get, but we make a life by what we give." In 22 brief and insightful essays, Richard B. Gunderman shows us that the key to more rewarding giving can be found by looking beyond mere donations of money. Exploring the ethical core of sharing and examining its importance for both those who receive and those who give, here is a book to deepen our understanding of what it means to share.